'Compressed Baby Head': A New 'Abusive Head Trauma' Entity? - Enrica Macorano; Mattia Gentile; Giandomenico Stellacci; Mariano Manzionna; Federica Mele; Mariagrazia Calvano; Mirko Leonardelli; Stefano Duma; Giovanni De Gabriele; Alessandro Cristalli; Raffaella Minella; Aldo Di Fazio; et al. (MDPI AG, 2023)
Background: Child abuse represents an important issue in the medico-legal and social context. In the last few decades, various aspects and mechanisms have been identified in child abuse case studies; however, constant research is needed in the field. With this paper, the authors will present a case of a new entity of Abusive Head Trauma that has come to the attention of medico-legal experts. Discussion: The trauma analysis performed on the cranio-encephalic district of the baby revealed quite peculiar lesions that led the authors to exclude that the injuries had been solely caused by violent shaking of the baby's head, as suggested by Shaken Baby Syndrome. Instead, the authors hypothesised that another lesion mechanism had been added to this one, namely latero-lateral cranial compression. The comprehensive and exhaustive analysis of the case led the authors to present a new possible entity in child abuse trauma, namely 'Compressed Baby Head'. Conclusions: To the best of our knowledge, in the current literature, no similar clinical cases have ever been described. Thus, the case's uniqueness deserves to be brought to the attention of experts and the entire scientific community, as well as medical personnel, paediatricians, and reanimators. These professional figures are the first individuals who may encounter complex clinical cases such as the one presented in this paper; thus, they need to know how to properly manage the case and ensure protection for the abused infants and children.